Challenging the Inevitable: Anatomy of a Suicide at the Royal Court Theatre London [Anatomy of a Suicide, Katie Mitchell] - Rayner, Francesca (2018)
Crítica ao espectáculo Anatomy of a Suicide. Author: Alice Birch. Director: Katie Mitchell. Set designer: Alex Eales. Costume designer: Sarah Blenkinsop. Lighting designer: James Farncombe. Composer: Paul Clark. Sound designer: Melanie Wilson. Associate director: Lily McLeish. Assistant director: Grace Gummer. Casting director: Amy Ball. Production manager: Marty Moore. Costume supervisor: Lucy Walshaw. Company manager: Joni Carter. Deputy stage manager: Sophie Rubenstein. Assistant stage manager: Louise Quaeermain. Stage management work place‑ ment: Robert Fletchr. Chaperone: Grace Osborne. Cast: Gershwyn Eustache Jnr. (Jamie), Paul Hilton (John), Peter Hobdaay (Dan/Dave/Felix/Luke/Nick), Adelle Leonce (Bonnie), Sarah Malin (Daisy/Diane/Emma/Esther/Karen/May), Jodie McNee (Jo/Laura/Lola), Hattie Morahan (Carol), Kate O’Flynn (Anna), Sophie Pettit, Vicki Szent‑Kirallyl (Anna/Daisy/Louise), Dickson Tyrell (Tim/Toby/Steve/ Mark). Place and date of premiere: Royal Court Theatre (Jerwood Theatre Downstairs), 3rd June, 2017.